2020
DOI: 10.3389/fbioe.2020.00446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acellular Amnion With Increased TGF-β and bFGF Levels on the Biological Behavior of Tenocytes

Abstract: The human amniotic membrane has been a subject for clinical and basic research for nearly 100 years, but weak rejection has been reported. The purpose of this research is to remove the cellular components of the amnion for eliminating its immune-inducing activity to the utmost extent. The amniotic membrane treated by acid removed the epithelial cell, fibroblast, and sponge layers and retained only the basal and dense layers. In vitro, biological effects of the new material on tenocytes were evaluated. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Cytokines-mediated inflammation response is a hallmark of immune system up-regulation ( 43 , 44 ). It is largely acknowledged that the inflammation could be aggravated by increasing the transcription levels of pro-inflammatory cytokines and decreasing the transcription levels of anti-inflammatory cytokines in fish, which were regulated by NF-κB and TOR ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines-mediated inflammation response is a hallmark of immune system up-regulation ( 43 , 44 ). It is largely acknowledged that the inflammation could be aggravated by increasing the transcription levels of pro-inflammatory cytokines and decreasing the transcription levels of anti-inflammatory cytokines in fish, which were regulated by NF-κB and TOR ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then monocytes differentiate into macrophages, with macrophages engulfing some of the necrotic cells and activating tendon cells, which act together at the site of injury ( Yang et al, 2022 ). After a few days, the cell proliferation phase begins, with fibroblasts and endogenous tenocytes act together on the damage area, where there is more type III collagen than type I collagen ( Leadbetter, 1992 ; Leong et al, 2020 ; Sang et al, 2020 ). bFGF can enhance type III collagen synthesis in the early phase of tendon healing, while it can promote type I collagen synthesis in the later phase.…”
Section: The Mechanisms Of Basic Fibroblast Growth Factor In Tendon H...mentioning
confidence: 99%
“…These results indicate that TGF-β1 is involved in the fibrosis of bladder tissue. An in vitro study showed that bFGF upregulates the expression of Collagen I ( 13 ). However, the mechanism underlying NB fibrosis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%